2019
DOI: 10.1177/0363546519889040
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of Graft Bridging and Superior Capsule Reconstruction for Large to Massive Rotator Cuff Tears: A Systematic Review

Abstract: Background: Graft bridging (GB) and superior capsule reconstruction (SCR) were developed to treat large to massive rotator cuff tears (RCTs); however, the outcome differences between GB and SCR remain unclear. Purpose: To systematically review and compare the outcomes of GB and SCR for large to massive RCT. Study Design: Systematic review. Methods: A systematic review was performed via a comprehensive search of PubMed, Embase, and the Cochrane Library. Studies of GB or SCR were included according to the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
(155 reference statements)
0
19
0
Order By: Relevance
“…The IG group showed significantly lower pain VAS, higher ASES score, and better active FF, ER at side, and IR at final follow-up (all P < .001). On comparing the mean differences 30 between pre- and postoperative functional outcome scores and active ROM, we found the IG group showed significantly improved pain VAS score, Constant score, and active FF and IR (all P < .001). Although there was no difference in the final Constant score between groups, the mean difference was significantly higher in the IG group, indicating greater improvement in Constant scores postoperatively compared with the SCR group.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The IG group showed significantly lower pain VAS, higher ASES score, and better active FF, ER at side, and IR at final follow-up (all P < .001). On comparing the mean differences 30 between pre- and postoperative functional outcome scores and active ROM, we found the IG group showed significantly improved pain VAS score, Constant score, and active FF and IR (all P < .001). Although there was no difference in the final Constant score between groups, the mean difference was significantly higher in the IG group, indicating greater improvement in Constant scores postoperatively compared with the SCR group.…”
Section: Resultsmentioning
confidence: 91%
“…Two recent systematic reviews 30 , 55 have evaluated IG and SCR for massive irreparable RCTs. Wall et al 55 reviewed 16 articles published from 2014 to 2017 and documented the surgical techniques and the results of several biomechanical and animal studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 In the present study, we found clinical features (Tables 3 and 4, Appendix A2) in terms of clinical and structural outcomes in shoulders with low-and high-grade massive RCTs after the patch procedure. 38 Considering our results and the results of previous studies, 18,32,38 we believe that grading of massive RCTs based on the degree of fatty degeneration of the ISP can be useful for determining the appropriate treatment strategy among multiple treatment options for irreparable massive RCTs. 9 This study has 2 major strengths.…”
Section: Discussionmentioning
confidence: 57%